Analisis Tentang Putusnya Perkawinan karena Istri Murtad (Analisis Putusan Pengadilan Agama Sibuhuan No 255/PDT.G/2023/Sibuhuan ) - Ismail Nasution; Ali Ardin Nasution; Mahmudin Hasibuan (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The purpose of this study is to determine the dissolution of marriage due to wife M (Analysis of the Sibuhuan Religious Court Decision No. 255 / Pdt.D / 2023 / PA Sibuhuan). The usefulness of this study is expected to be useful information for researchers, especially in fulfilling the requirements for a Bachelor of Laws degree as well as a reference for similar researchers and can provide understanding and knowledge about the dissolution of marriage due to apostasy of the wife (analysis of the Sibuhuan Religious Court Decision No. 255 / Pdt.D / 2023 / PA Sibuhuan. This research is a field research, which is a research that is directly related to the object being studied. The method used in this study is a qualitative descriptive method. For data collection, the data collection instruments used are observation, interviews and documentation. The data processing is carried out by conducting a study of the theory of reality that exists at the research site. The results of the study concluded that: first, the judge's consideration in deciding the case of dissolution of marriage because the wife apostatized (analysis of the decision of the Sibuhuan Religious Court No. 255 / Pdt.D / 2023 / PA Sibuhuan, namely the applicant and respondent's family were not harmonious because since the applicant was sick and at that time the respondent decided to migrate to Pekanbaru City and when the respondent returned he had remarried and at that time the applicant decided to divorce the respondent because he had remarried and had apostatized and did not want to return to Islam. The applicant and respondent cannot be reconciled and have been going on continuously. Then the legal basis for the judge in deciding this case to be fasakh is Article 116 letter (h) of the compilation of Islamic law. The legal consequences arising from the fasakh decision are that the marriage contract is canceled absolutely, this indicates that the relationship between the two is legally broken and there is no longer a special bond or relationship. If during the iddah period, the wife has not repented, then she is not allowed to reconcile or enter into a new marriage contract. Other consequences of fasakh are: the wife does not receive a living, the child's position remains as a legitimate child, the obligation to care for the child, joint assets are divided fairly. And it also results in an apostate husband or wife not having the right to be the guardian of another Muslim person.